Indirect Determinants Analysis of the Protein Intake Status of Stunted Under-Five Children at the Kedundung Health Service, Mojokerto City, Indonesia - Syihabuddin, Muhammad; Katmawanti, Septa; Nilasari, Karina; Kurniawan, Agung (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
The highest prevalence of stunted in the Kedundung Health Center working area in Mojokerto City exceeds the Stunting Prevalence Threshold. Stunted is influenced by the adequacy status of nutritional intake consumed by children, especially the level of protein nutrition intake. Both indirect and direct factors influence protein intake status. This research aims to identify indirect factors using quantitative cross-sectional method. This research used secondary data on stunted under-five children at the Kedundung Health Center, with more than 48 under-five children. The sampling technique used is nonprobability-purposive sampling, which then eliminates missing data through technical data analysis using the Chi-square correlation test. The results obtained for the five independent variables studied, the variable family income level, the father’s education and the mother’s education, have a significant relationship. The father’s employment status variable can not be concluded. The father’s employment status in the literature is related to protein intake through the father’s role in regulating the low protein intake of under-five children. The mother’s employment status variable has no significant relationship with the intake status of under-five children. Mothers do not have sufficient knowledge and skills to regulate under-five children’s intake patterns, including prioritizing food spending and controlling the adequacy of protein intake. The implications of this study show that the family’s economic conditions and the parent’s knowledge affect the protein intake status of under-five children; also, regional financial stability impacts the family economy.